ТҮКТІ ОЙМАҚШАНЫҢ (Digitalis lanata Ehrh ) ОҢТҮСТІК ҚАЗАҚСТАНДА ӨСУ ЕРЕКШЕЛІКТЕРІ (Experimental biology, 2009)
In the result of researches established that at digitalis lanata Ehrh woolly seed efficiency depends on weather conditions of a season in which seeds were formed, quantities generatisch runaways, and also fromposition of boxes in an inflorescence and quantity and weight of seeds in them.
Keywords: digitalis lanata Ehrh